α1L-adrenoceptors mediate contraction of human erectile tissue - Beverley J. Davis; Christopher R. Chapple; Donna J. Sellers; Alisdair L. Naylor; David Sillar; Alistair Campbell; Russ Chess-Williams (Elsevier, 2018)
α1-adrenoceptor antagonists can impact upon sexual function and have potential in the treatment of erectile dysfunction. Human erectile tissue contains predominantly α1A-adrenoceptors, and here we examined whether contractions of this tissue are mediated by the functional phenotype, the α1L-adrenoceptor. Functional experiments using subtype selective agonists and antagonists, along with radioligand ([3H]tamsulosin) binding assays, were used to determine the α1-adrenoceptor population. A61603, a α1A-adrenoceptor agonist, was a full agonist with a potency 21-fold greater than that of noradrenaline. The α1A- and α1D-adrenoceptor antagonist tamsulosin antagonized noradrenaline responses with high affinity (pKD = 9.7 ± 0.3), whilst BMY7378 (100 nM) (α1D-adrenoceptor antagonist) failed to antagonize responses. In contrast, relatively low affinity estimates were obtained for both prazosin (pKD = 8.2 ± 0.1) and RS17053 (pKD = 6.9 ± 0.2), antagonists which discriminate between the α1A- and α1L-adrenoceptors. [3H]Tamsulosin bound with high affinity to the receptors of human erectile tissue (pKD = 10.3 ± 0.1) with a receptor density of 28.1 ± 1.4 fmol mg−1 protein. Prazosin displacement of [3H]tamsulosin binding revealed a single homogenous population of binding sites with a relatively low affinity for prazosin (pKi = 8.9). Taken together these data confirm that the receptor mediating contraction in human erectile tissue has the pharmacological properties of the α1L-adrenoceptor. Keywords: Erectile tissue, α1-adrenoceptor subtypes, α1L-adrenoceptor, Tamsulosin, Prazosin